Reflection and reflective spaces in the early years a guide for students and practitioners - Pendrey, Annie (Routledge, Taylor & Francis Group, 2023)
"Reflection and Reflective Spaces in the Early Years will support readers in developing their own reflective practice and creating reflective environments for the young children and families they work with. Combining case studies and reflective tasks to compliment a range of theories, concepts and alternative approaches to reflection, this book shows how the reflective process can help practitioners adapt to rapid changes in the sector and improve professional practice. Drawing on action research alongside the use of Japanese words and concepts (such as Ikigai, exploring your reason for being, Hansei, the art of honest self- reflection, and Wabi-Sabi, reflecting upon your perfectly imperfect self), chapters are full of practical guidance, activities and questions to prompt reflective thinking, covering such topics as: Reflection and Reflective Theory The Art of Self Reflection The Reflective Underground Creating Reflective Spaces in the Early Years The Rainbow Researcher Framework How to create reflective spaces in Early Years Exploring Creative Methods of Reflection This book will be invaluable reading for early years practitioners, tutors and early years students on level 3 courses and Foundation Degrees, but also for anyone interested in reflection or starting an academic or professional journey where you are required to reflect upon your practice"--